Cytogenomic profiling of chronic lymphocytic leukaemia patients using dna microarray - Zamri, Wan Norizzati Wan Mohamad (2021)
Chronic lymphocytic leukaemia (CLL) accounts approximately 5 – 11% of lymphoproliferative disorders in Western countries. Despite the indolent disease progression, it had been reported that Asian CLL is more aggressive and had shorter time to first therapy compared to Western counterpart due to its complex genomic landscape. Even though chromosomal aberration of CLL can be detected by Fluorescence in situ Hybridization (FISH) and Multiplex Ligation-dependent Probe Amplification (MLPA) together with conventional cytogenetic analysis (CCA), however some of the abnormality can be missed due to method’s limitation. This study investigated chromosomal aberration using DNA microarray to detect cryptic chromosomal abnormality that could escape detection of FISH and MLPA which able to overcome both methods limitation and subsequently identify candidate genes that could involve in our population CLL. In this retrospective study, archive genomic DNA of 7 newly diagnosed CLL in 2012 from previous study (USM Short Term grant title: Analysis of Hypermethylation Status of Tumor Suppressor Genes p16INK4a, p15INK4b, ADAM12 and PCDHGB7 in Chronic Lymphocytic Leukemia Patients and Normal Individuals)(JEPeM code: USMKK/PPP/JEPeM/234.3(07)) were used. They were subjected to DNA microarray analysis using Affymetrix CytoScan® 750K Array using manufacture procedure. Detailed clinical information was extracted from patient’s cytogenetic request form and patient’s medical records. Chromosomal aberration were identified in all patients using DNA microarray. Result showed deletion of chromosome 13q and 14q varied in size ranging 0.42MB to 39.97MB. Interestingly, there were also additional CAs in form of trisomy 3, cryptic interstitial deletion of chromosome 13q, 14q, 16p, Xp and duplication of 14q32.33 and 22q11.2. Deletion 14q32.33 region closely related to mutational status of IGH while other cryptic aberrations need further investigation to explore contribution to CLL pathogenesis. All the cryptic deletion and duplication of these chromosome unable to be detected by CCA due to small size (<5MB). The findings can help the clinicians to stratify patients accordingly and more close monitoring warranted. DNA microarray are valuable tool in detecting relevant genomic aberrations in CLL patients especially cryptic abnormalities. Implementation of DNA microarray in CLL diagnosis will help clinicians to give precise treatment that tailored to patient’s need.